2017
DOI: 10.1038/ejhg.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of years of life after diagnosis of breast cancer using omics and omic-by-treatment interactions

Abstract: Breast cancer (BC) is the second most common type of cancer and a major cause of death for women. Commonly, BC patients are assigned to risk groups based on the combination of prognostic and prediction factors (eg, patient age, tumor size, tumor grade, hormone receptor status, etc). Although this approach is able to identify risk groups with different prognosis, patients are highly heterogeneous in their response to treatments. To improve the prediction of BC patients, we extended clinical models (including pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…Similarly, in a maize diversity panel, genomic prediction models that combined transcript and marker data only outperformed models using markers alone for certain traits (Guo et al, 2016). Finally, efforts to integrate additional omics information to predict various traits in Drosophila melanogaster (Li et al, 2019) and human diseases, such as breast cancer (González-Reymúndez et al, 2017), and responses to treatment interventions, including acute kidney rejection and response to infliximab in ulcerative colitis (Kang et al, 2017;Zarringhalam et al, 2018), have demonstrated the potential usefulness of transcriptome data in the field of precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a maize diversity panel, genomic prediction models that combined transcript and marker data only outperformed models using markers alone for certain traits (Guo et al, 2016). Finally, efforts to integrate additional omics information to predict various traits in Drosophila melanogaster (Li et al, 2019) and human diseases, such as breast cancer (González-Reymúndez et al, 2017), and responses to treatment interventions, including acute kidney rejection and response to infliximab in ulcerative colitis (Kang et al, 2017;Zarringhalam et al, 2018), have demonstrated the potential usefulness of transcriptome data in the field of precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a maize diversity panel, GP models that combined transcript and marker data only outperformed models using markers alone for certain traits 16 . Finally, efforts to integrate additional omic information to predict various traits in Drosophila melanogaster 17 , and human diseases, such as breast cancer 18 , and responses to treatment interventions, including acute kidney rejection and response to infliximab in ulcerative colitis 19,20 , have demonstrated the potential usefulness of transcriptome data in the field of precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Samples correspond to biopsies from primary tumor (breast) conserved as frozen tissue, and taken before patients underwent treatment. A total of 284 deaths occurred within four years after diagnosis (based on the time of maximum prediction accuracy of survival time for this data set [14], across different cancer subtypes: 131 luminal (40% deceased at fourth year), 431 triple negative (28%) and 131 Her2 + subtype (10%)). In this study, tumor grade was grade one (n = 950), grade two (n = 775), and grade three (n = 169), while tumor sizes ranged from 0.17 to 1.82 cm of diameter.…”
Section: Study Population and Samplementioning
confidence: 99%
“…The final number of genes after quality controls was 19,535. More detail about cohort and edition criteria can be found elsewhere [12,14]. The current study uses anonymized data accessed through Synapse (https://www.…”
Section: Study Population and Samplementioning
confidence: 99%